DISIPLIN SISWA MENGIKUTI KEGIATAN PRAMUKA SEBAGAI EKSTRAKURIKULER DI SMP TRI BHAKTI PEKANBARU - Ramadani Takengon Takengon; Jaspar Jas Jas; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problems of this study is how high discipline scout activity as students follow a curriculum in junior Tri Bhakti Pekanbaru. The purpose of this study was to determine the stage of activity scout discipline students follow a curriculum in junior Tri Bhakti Pekanbaru, the benefits of this research as a useful input materials and can give comprehension to students to extracurricular activities scout. The population in this study as many as 90 people people learn and study sample is 47 people dambil using random sampling techniques. Data collection instrument that is a questionnaire with 54 statements and after the trial lived 41 legitimate statement to be made in the study instrument. Data analysis through quantitative descriptive analysis. From the calculation results obtained retort offerings based indicators of future ability to comply with the phase of the high discipline of 84.78%, and the lower stage of discipline as much as 14.65%, pointing comply with the regulations that apply activity-activity that discipline stage high of 91.45% , and the lower stage of discipline as much as 9.7%, pointing responsibility for the tasks given to the discipline stage high of 88.14%, and the lower stage of discipline as much as 11.86%, bookmark submitting to scout the stage Satya discipline and a high of 84.03% discipline stage lower by 15.16% by value and comply with applicable norms that discipline the stage higher by 91.29% and stage discipline as much as 8.7% lower. Key words: Discipline, Discipline Students, Extracurricular Scouts